MORPHOLOGY, BIOECOLOGY, PHARMACOLOGICAL PROPERTIES OF THE MEDICINAL PLANT ACORUS CALAMUS AND ITS USE IN FOLK MEDICINE - Jangabaeva Aygul; Saparbaeva Farangiz (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The flora of Uzbekistan is very rich and diverse. Deserts and steppes, mountains and hills, lowlands and river deltas are located side by side to create a wonderful landscape. The rich flora of the country includes more than six thousand different plants, including medicinal plants. Such herbs are environmentally friendly and are used as raw materials for the production of food, aromatic and pharmaceutical products. This article provides information on the morphology, bioecology, and medicinal properties of the medicinal plant Acorus calamus, as well as its use in folk medicine.